Dividend tax cuts in the United States and single-tier tax regime in Malaysia: share price reactions to tax policy changes - Selamat, Aslam; Mohamed Ariff,; Ramadilli Mohd, Shamsher Mohamad (Universiti Putra Malaysia Press, 2012)
There is a body of received theories which suggest that tax policy changes actually influence the value of corporations, and affect capital market values. There is strong evidence of share price being changed whenever good or bad news from tax changes occur. This paper provides a very short review of well-known theories, with the aim of showing how tax changes relating to dividends in Malaysia and in the USA do actually affect the values of shares in one mid-income and one high-income economy. Malaysia’s policy change in 2007 to streamline the dividend credit system into a single-tier tax system led to share price increases in Bursa Malaysia. Tax effect in the USA was tested using the good news of dividend tax cuts passed into law on three dates over 2003 and 2010. These findings are very much policy relevant for the ongoing debate, for example, in Malaysia on introducing future goods and sales tax to reduce other taxes.